NGG Notes Graphics user interface Gallery / Leong Pek Ling - Leong , Pek Ling (1999)
Nowadays, the user interfaces for most system involves graphics. Notes Graphics User Interface Gallery (NGG) is a toolkit developed to support interactive user interface design for the applications of Lotus Notes. This toolkit is used in Lotus Notes application to assist the programmers to design interfaces or menus for their application. The development of NGG proves that it is more attractive to apply graphics on user interface. Before developing NGG, researches about all the features for user interface in Lotus Notes was done. Notes GUl Gallery consists of two components, where the first component is a library of graphics, such as lines, buttons, icons and pictures. These graphics can be copied and pasted into Lotus Notes design elements such as Navigators, Layout Regions and Forms. Another component of NGG is a collection of templates for navigators and forms. The objective of this project is to assist developers to build applications in a faster and easier way so that they can focus on the system design and development tasks. NGG was developed using Lotus Notes Release 4.6 software to create and store database of templates and graphics. The graphics section of this toolkit can be used for other applications rather than Lotus Notes. It is believed that toolkit of this nature will gradually become essential to everyone in the future.